Fraud Prevention: The Contribution of Internal Control, Internal Audit, and Organizational Culture - Yulfani; Ansar, Muhammad; Yamin, Nina Yusnita; Paranoan, Selmita; Gunarsa, Arif (PT Mattawang Mediatama Solution, 2025)
Losses within organizations often stem from fraudulent activities, with fraud levels significantly increasing, particularly in the public sector. This study aims to examine the contributions of internal control, internal audit, and organizational culture to fraud prevention efforts at the Regional Inspectorate Office of Central Sulawesi Province. A numerical analysis using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach was applied to 35 auditors as respondents. The findings indicate that internal control and internal audit do not significantly contribute to fraud prevention efforts. However, organizational culture plays a substantial role in preventing fraud. These results suggest the necessity of enhancing understanding regarding the implementation of organizational culture in fraud prevention, both in public and private institutions. Nevertheless, despite their lack of statistical significance, internal control and internal audit remain inseparable components in the broader effort to prevent fraud and organizational losses. Therefore, institutions must reinforce each audit-related element to mitigate the risks of fraud. In conclusion, the study underscores that organizational culture is the most crucial factor in preventing fraud. Thus, strengthening values such as integrity, transparency, and accountability must be prioritized in any anti-fraud strategy.